Geliat Pariwisata Wellness Tourism Dalam Masa Pandemi - Umar Abdul Jabbar; Andhi Supriyadi (Universitas Katolik Widya Karya Malang, 2023)
One of the industries that has been badly impacted by the COVID-19 outbreak is tourism. According to BPS statistics from 2021, there has been a dramatic drop in both domestic and international tourism. Diverse initiatives are made to keep Indonesian tourism alive. Kemenparekraf/Baparekraf is in charge of the